Survei Self Confidence Pembelajaran Senam Lantai pada Siswa di MTs Al Kautsar Kabupaten Karawang - Deni Adlan; Abdul Salam Hidayat; Fahrudin Fahrudin (Universitas Singaperbangsa, 2021)
This research aims to determine the confidence of front roll back and tiger jump in learning floor exercise for students at MTS Al Kautsar, Karawang Regency. This research is a descriptive reserch, the method used in this research techniques using a questionaire (questionaire). The population in this study were all students of class VIII at MTS Al Kautsar, Karawang Regency. This study uses a population sampling technique. Samples of this study were all students of class VIII at MTS Al Kautsar, Karawang Regency, as many as 69 students consisting of 41 male students and 28 female students. Data analysis used descriptive method with percentage calculation. Based on the result of this study, it shows the confidence of front roll back roll and jump tiger in learning floor gymnastics for students at MTS Al Kautsar, Karawang Regency for male stidents, the greatest is in the “high” category, amounting to 87.80% (36 students), while the level of confidence female students are in the high category with a percentage of 89.29% (25 stundents). Keywords: Self-confidence, Rool Back and Jump Tiger